Exercise physiology : theory and application to fitness and performance - Powers, Scott K. (Scott Kline), 1950-; Howley, Edward T., 1943- (New York : McGraw-Hill, 2012)
'Written especially for exercise science and physical education students, this text provides a solid foundation in theory illuminated by application and performance models to increase understanding and to help students apply what they've learned in the classroom and beyond.'--
Buku Bacaan Asas Fakulti.
Includes index.
Keywords: Exercise -- Physiological aspects; Exercise -- Physiology aspects